THE IMPACT OF USING VIDEO LEARNING MEDIA ON MATHEMATICS LEARNING OUTCOMES FOR FIFTH-GRADE STUDENTS AT SD N 01 RANAH PESISIR - Rismaini, Lili; S, Faeza Rezi (Jurnal Ilmu Pendidikan Ahlussunnah, 2024)
learning. The rapid advancement of information technology in recent years has significantly transformed societal paradigms in accessing and acquiring information. These technological advancements have also influenced educational media, with teachers frequently utilizing video media in instruction. The objective of this research is to improve student learning outcomes through the effective application of video media in mathematics education. This research is categorized as a quantitative study employing a quasi-experimental method. It was conducted with fifth-grade students at SD N 01 Ranah Pesisir. The research instrument was designed to evaluate the effectiveness of video learning media in mathematics education. The findings of this study, analyzed using the Paired Sample Test statistical method, indicate a significance value (2-tailed) of 0.000, which is below the alpha value of 0.05. This result signifies that the Sig. 2-tailed value (0.000) is less than the alpha value (0.05), leading to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Hi). Thus, there is a significant difference in students' mathematics learning outcomes before and after the implementation of video learning media.